Explaining infrastructure underperformance in Brazil: cash, political institutions, corruption, and policy Gestalts. (4th May 2017) - Armijo, Leslie Elliott; Rhodes, Sybil D.
ABSTRACT: Brazil's infrastructure underperforms compared to that of peer emerging economies. Why? The political institutions of coalitional presidentialism with strong federalism undermine rational national planning. Politicians' incentives to distribute 'pork' combine with sector-specific oligopoly characteristics, offering fertile ground for corruption. Yet the greatest challenge is low infrastructure investment, a consequence of weak private capital markets and regulatory inconsistency. Recent center-right governments improved infrastructure service delivery without stimulating investment, while center-left governments raised investment, but undermined public finances and efficiency. Greater technocratic consensus across the partisan divide on reforms to stimulate investment is one positive consequence of Brazil's current crisis.